Oral Cannabinoid Preparations for the Treatment of Chronic Migraine: A Retrospective Study. Issue 2 (4th August 2021) - Baraldi, Carlo; Lo Castro, Flavia; Negro, Andrea; Ferrari, Anna; Cainazzo, Maria Michela; Pani, Luca; Guerzoni, Simona
Abstract: Objective: To explore the effectiveness and safety of three oral cannabinoid preparations (FM2 ®, Istituto farmaceutico militare, Firenze, Italy; Bedrocan ®, Bedrocan International, Vandaam, Netherlands; and Bediol ®, Bedrocan International, Vandaam, Netherlands) in the treatment of chronic migraine. Design: Retrospective, cohort study. Subjects: Patients with chronic migraine who received FM2, Bedrocan, or Bediol daily for the off-label treatment of their headache, for up to 6 months. Methods: The number of migraine days per month, pain intensity, the number of acute medications taken per month, the number of days per month on which the patient took at least one acute medication, and adverse events were recorded at baseline and at 3 months and 6 months after the start of treatment with oral cannabinoid preparations. Results: The number of migraine days did not change significantly after the third month or the sixth month when compared with baseline ( P = 0.1182). The pain intensity ( P = 0.0004), the acute medication consumption ( P = 0.0006), and the number of days per month in which patients took at least one acute medication significantly decreased when compared with baseline ( P = 0.0004). No significant differences were found between patients who were still taking a preventive treatment for chronic migraine and those who were not (all P > 0.05). Different oral cannabinoid preparations displayed similar levels of effectiveness (all P > 0.05). The adverse events were mostly mild and occurred in 43.75% of patients. Conclusions: Oral cannabinoid preparations may have a role in reducing pain intensity and acute medication intake in patients with chronic migraine, but the magnitude of the effect seems modest; further studies are needed.